Analysis of the Influence of IoT Server Robots, Operational Management Systems, And Electric Car CAS on Improving Service Efficiency In Sharia Perspective: (Study on El's Coffee Roastery Bandar Lampung) - Juwita Ariana; Anas Malik; Nurhayati (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study was conducted to analyze the importance of implementing digital technology in improving service efficiency in the modern café industry, particularly through the use of Internet of Things (IoT)-based service robots, operational management systems, and electric vehicle charging facilities from a Sharia business perspective at El's Coffee Roastery in Bandar Lampung. This study aims to measure and analyze the influence of these three variables on service efficiency improvement. The method used is quantitative research with an associative approach, employing accidental sampling on 97 respondents. Primary data was collected through the distribution of a Likert-scale questionnaire and analyzed using multiple linear regression with the assistance of IBM SPSS 27. The results indicate that, individually, the IoT service robot has a positive and significant effect on service efficiency (t = 7.397; sig. 0.000), the operational management system has a positive and significant effect (t = 6.512; sig. 0.000), and the electric vehicle charging station also has a positive and significant effect (t = 2.555; sig. 0.012). Simultaneously, all three variables have a significant effect on service efficiency (F = 41.301; sig. 0.000) with a contribution of 55.7%. A synthesis of the research findings confirms that the integration of modern technology, when managed professionally, can create services that are effective, efficient, and aligned with the principles of maslahah, amanah, and hifz al-bi'ah in Islamic business. The policy implications of this research encourage business operators to adopt sustainable technological innovations that remain grounded in Islamic values in order to enhance business competitiveness.